Public Image of Ukrainian Customs: Trying to Lead a Camel through the Eye of a Needle - Кормич, Людмила Іванівна; Кормич, Л. І.; Kormych, Liudmyla I.; Краснопольська, Тетяна Миколаївна; Краснопольська, Т. М.; Krasnopolska, Тetiana М.; Кормич, Анатолій Іванович; Кормич, А. І.; Kormych, Anatolii I. (Odesa : Publishing House Helvetica, 2024)
The World Customs Organization recommends that national customs prioritize branding and reputation management. In Ukraine, the customs authorities have been consistently ranked as one of the most corrupt sectors of public life, leading to negative perceptions. The article discusses the various factors that affect the public perception of customs, such as how the institution portrays itself and how it is perceived by the media, stakeholders, and the general public. Evidence suggests that the perception of Ukrainian customs authorities has improved slightly due to their effective response to the wartime challenges and their success in aligning with EU customs legislation. In addition, Ukrainian customs has recently significantly strengthened its reputation management through media and social networks, close cooperation with stakeholders, and taking an active public stance. However, the reputation risks remain incredibly high.
Kormych L. Public Image of Ukrainian Customs: Trying to Lead a Camel through the Eye of a Needle / L. Kormych, T. Krasnopolska, A. Kormych // Lex Portus. – Odesa : Publishing House Helvetica, 2024. – 10(1). - P. 30–40. URL: https://doi.org/10.26886/2524-101X.10.1.2024.2
Keywords: public image; reputation; branding; Customs authorities; public administration reform; corruption; reputation management; Ukraine